A survey-based study about burnout among postgraduate medical trainees: implications for leaders in healthcare management - Yacoubian, Aline; Demerouti, Evangelia; Degheili, Jad A.; El Hajj, Albert (Frontiers in Public Health, 2023)
Introduction The goal of the study is to assess burnout among postgraduate medical trainees, evaluate the association with sociodemographic features and offer potential wellness strategies for leaders responsible for their education, training, management, and wellbeing. Methods The Oldenburg Burnout Inventory was used. The web-based, voluntary, and anonymous survey was sent to postgraduate medical trainees from various specialties and all years of training in a tertiary medical center in Beirut, Lebanon. Additional questions were added after the survey regarding reporting channels for burnout and possible interventions for wellbeing. Results The total number of valid responses are 188. The prevalence rates of high burnout are 37.2% for disengagement and 51.1% for exhaustion. There is a significant difference between the mean of exhaustion and gender (p = 0.003). There is a significant difference between the mean of disengagement and year of training (p = 0.017). There is a significant difference between the mean of exhaustion and year of training (p = 0.029). There is a significant difference between the frequency of disengagement and year of training (p = 0.027). Conclusion The study reveals how postgraduate medical training program is impacted by the existing challenges from social, health, and financial standpoint, along with the instabilities encountered such as multiple wars and port blast in 2020 and how these variables aggravate burnout. Burnout severely impacts the education and training of PGMT and promoting wellbeing can help reverse the process. Findings contribute to establishing effective strategic interventions for leaders in healthcare management to adopt.